(untitled) (Cuadernos de Extensión Universitaria de la UNLPam, 2024)
Systematization of universitary extension experiences is an essential issue for the effective interchange of knowledge among several institutions. Knowledge interchange is a priority when it involves the life quality of populations, the protection of natural ecosystems and the benefits they provide. From the University Technician in Park Rangers of the Faculty of Tourism and Environment of the Provincial University of Córdoba, we developed the project Helping the Native Forest, which addresses the problem of the invasion of invasive exotic plant species in two protected areas of the Chaco ecosystem of Córdoba . The objective of this article is the systematization of environmental knowledge interchange and actors involved in the traits developed in the project. We describe different levels of interaction among institutions and people that were involved in the project; and aspects to consider to implement universitary extension actions in the future.